PELATIHAN DAN SIMULASI DELF BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA PRANCIS UNTUK MENGHADAPI UJIAN SESI NOVEMBER 2025 - Trisna, Indah Nevira; Rini, Setia; Ikhtiarti, Endang; Rosita, Diana; Kusrini, Nani (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2026)
The lack of motivation and preparation among some students in the French language education program at the University of Lampung in taking the DELF test is a serious problem. This program is designed to improve students' competence in the four main skills tested in DELF: Compréhension orale (listening), Compréhension écrite (reading), Production orale (speaking), and Production écrite (writing). Through a systematic approach, students will be equipped with a deep understanding of the exam format, question-answering techniques, and effective time management strategies. The simulations, which are provided regularly and routinely, have proven to help students achieve higher scores and a better understanding of DELF questions. In the simulations that have taken place, there has been a significant increase in the number of students who passed the post-test compared to the pre-test. In line with the goal of preparing students, the DELF simulations can be said to have been successful in preparing students to take the DELF exam in the November 2025 session.   Kurangnya motivasi dan persiapan sebagian mahasiswa program studi pendidikan bahasa prancis Universitas Lampung dalam mengikuti tes DELF merupakan suatu masalah yang cukup serius. Program ini dirancang untuk meningkatkan kompetensi mahasiswa dalam empat keterampilan utama yang diuji dalam DELF: Compréhension orale (mendengarkan), Compréhension écrite (membaca), Production orale (berbicara), dan Production écrite (menulis). Melalui pendekatan yang sistematis, mahasiswa akan dibekali dengan pemahaman mendalam mengenai format ujian, teknik pengerjaan soal, serta strategi manajemen waktu yang efektif. Simulasi yang diberikan secara berkala dan rutin terbukti membantu mahasiswa dalam meraih skor dan pemahaman terhadap soal delf. Pada kegiatan simulasi yang telah berlangsung terdapat kenaikan signifikan jumlah mahasiswa yang lolos pada saat post test dibandingkan dengan pretest. Sesuai dengan tujuan memberi kesiapan, simulasi delf dapat dikatakan berhasil untuk mengantarkan mahasiswa mengikuti ujian delf pada sesi November 2025.